Anesthetic management of minimally invasive intervention in children's oncohematology: preoperative patient management protocol - V. V. Shchukin; E. A. Spiridonova; V. V. Lazarev; A. V. Khar'kin; L. E. Tsypin; V. L. Ayzenberg (Онкогематология, 2014)
Preoperative patient management protocol in the complex anesthetic support of minimally invasive interventions in pediatric oncology is described. Choice of general anesthesia method was determined by the specific clinical situation by analyzing all of the following factors: airway management, necessity and anticipated duration of unconsciousness, the need for analgesia, necessity and duration of immobilization, prevention of hypothermia, the presence and severity of disturbances in the hemostatic system, comfort for the child and his representatives (parents). Basic techniques of child preoperative examination, as well as the methodology for predicting the risk of perioperative adverse events are described.